(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Today, the most important problem for all countries of the world is the provision of electricity to the needs of the population and the industrial sector. Due to low water, the volume of electricity production at hydroelectric power plants in Uzbekistan has decreased by 23% this year, as in the countries of Central Asia [1]. According to statistics, in the Republic of Uzbekistan, when generating electricity in 2021, the RES capacity was 2,147 MW. The share of hydropower was 2043 MW (95%) [2].